Human Cytomegalovirus Infections Are Associated With Elevated Biomarkers of Vascular Injury - Styles, Jennifer N.; Converse, Reagan R.; Griffin, Shannon M.; Wade, Timothy J.; Klein, Elizabeth; Nylander-French, Leena A.; Stewart, Jill R.; Sams, Elizabeth; Hudgens, Edward; Egorov, Andrey I. (Frontiers in Cellular and Infection Microbiology, 2020)
Background: Human cytomegalovirus (HCMV) infects approximately 50% of adults in the United States. HCMV infections may cause vascular inflammation leading to cardiovascular disease, but the existing evidence is inconsistent. Objective: We investigated demographic predictors of HCMV infection and explored associations between HCMV infection status, the intensity of anti-HCMV Immunoglobulin G (IgG) antibody response, and biomarkers of inflammation and endothelial function which are known predictors of cardiovascular disease. Methods: We conducted a cross-sectional study of 694 adults residing in the Raleigh-Durham-Chapel Hill, NC metropolitan area. Serum samples were tested for IgG antibody response to HCMV, and for biomarkers of vascular injury including soluble intercellular adhesion molecule 1 (sICAM-1), soluble vascular cell adhesion molecule 1 (sVCAM-1), C-reactive protein (CRP), and serum amyloid A (SAA). Associations between HCMV and biomarker levels were analyzed using two approaches with HCMV serostatus modelled as a binary variable and as an ordinal variable with five categories comprised of seronegative individuals and quartiles of anti-HCMV antibody responses in seropositive individuals. Results: HCMV seroprevalence in the study population was 56%. Increased body mass index, increased age, female gender, racial/ethnic minority status, and current smoking were significantly associated with HCMV seropositivity in a multivariate regression analysis. HCMV seropositivity was also associated with 9% (95% confidence interval 4% - 15%) and 20% (0.3% - 44%) increases in median levels of sICAM-1 and CRP, respectively, after adjusting for covariates. The association between HCMV seropositivity and median levels of sVCAM-1 and SAA were positive but not statistically significant. Significant positive associations were observed between the intensity of anti-HCMV IgG responses and levels of sICAM-1 and sVCAM-1 (p-values 0.0008 and 0.04 for linear trend, respectively). To our knowledge, this is the first epidemiological study to show a relationship between anti-HCMV IgG responses and vascular injury biomarkers sICAM-1 and sVCAM-1 in the general population. Conclusion: HCMV infections are associated with vascular injury and inflammation biomarkers in adult residents of North Carolina.